2017
DOI: 10.1111/jen.12421
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Serratia marcescens with insecticidal activity from Polyphylla olivieri (Col.: Scarabaeidae)

Abstract: Members of the genus Serratia are known for their abilities to infect insects. In this study, a red-pigmented S. marcescens was isolated and characterized from the infected larvae of Polyphylla olivieri using bacterial cultivation, phylogenetic analysis as well as bioassays against larvae of the two insect pests, Plodia interpunctella and Ephestia kuehniella. Comparative 16S rRNA and groEL gene sequence BLAST analyses strongly suggested that the isolated strain should be placed in the genus Serratia, sharing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
(50 reference statements)
0
14
0
1
Order By: Relevance
“…Chitinolytic bacteria have been correlated with insect biocontrol [23] and considered as a source of useful bioactive molecules and genes for this application [24]. Insect chitinases play a critical role in insect growth and development, and their overexpression at appropriate times could disrupt the cuticle and/or gut physiology in many insect species leading to negative effects and even death [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitinolytic bacteria have been correlated with insect biocontrol [23] and considered as a source of useful bioactive molecules and genes for this application [24]. Insect chitinases play a critical role in insect growth and development, and their overexpression at appropriate times could disrupt the cuticle and/or gut physiology in many insect species leading to negative effects and even death [25].…”
Section: Introductionmentioning
confidence: 99%
“…Insect chitinases play a critical role in insect growth and development, and their overexpression at appropriate times could disrupt the cuticle and/or gut physiology in many insect species leading to negative effects and even death [25]. In fact, the usage of Gram negative bacterial strains like S. marcescens has been observed to be a great biocontrol agent against Spodoptera litura at different developmental stages [24,26], due to its ability to produce different chitinolytic enzymes [27]. In this way, the search for chitinolytic enzymes produced in transgenic plants with insecticidal activity is of scientific interest.…”
Section: Introductionmentioning
confidence: 99%
“…Serratia marcescens is present as part of the gut microbiota of some sandflies and triatomine species [ 11 ]. Examples of S. marcescens , isolated as a pathogen from insects of the orders Coleoptera, Diptera, Orthoptera, and Lepidoptera, have been reported [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Similarly, P. aeruginosa has been isolated from different weevil species (the pecan weevil Curculio caryae [ 14 ]; the southern pine weevil Dendroctonus brevicomis [ 12 ]; the red palm weevil Rynchophorus ferrugineus [ 19 ], the tobacco and tomato hornworms Manduca sexta and M. quinquemaculata [ 20 ], from Schistocerca gregaria eggs [ 21 ] in the wild and from several other insect species.…”
Section: Introductionmentioning
confidence: 99%
“…According to Krishanti et al (2017), BLSP4 and BLSP3 were identified as Serratia marcescens (similarity 94%) and Staphylococcus sciuri (similarity 99%) respectively through molecular identification of the gene encoding 16S rDNA. Serratia (Monica et al, 2015), Plodia interpunctella and Ephestia kuehniella fifth instar larvae (Bidari et al, 2017), and also Spodoptera litura (Aggarwal et al, 2015). Meanwhile, the Staphylococcus sciuri species group consists of five species that are most often regarded as commensal animal-associated bacteria.…”
Section: Results and Discussion Entomopathogenic Bacterial Isolatesmentioning
confidence: 99%